PENGARUH STRES KERJA, KOMPENSASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA PT ATELIER 6 JAKARTA - Bagy Arya Sadewo (2021)
This research is a quantitative study that aims to determine and prove the effect of work stress, compensation and career development on employee performance at PT Atelier 6 Jakarta. in the Covid 19 Pandemic Period. This study used a sample of 38 respondents, namely employees of PT Atelier 6 Jakarta. The analytical technique used in this research is the Coefficient of Determination Test, T Test (Partial) and F Test (Simultaneous) using Smart PLS 3.0 software. The test results obtained (1) Job stress has a significant effect on employee performance at PT Atelier 6 Jakarta (2) Compensation has no effect and is not significant on employee performance at PT Atelier 6 Jakarta, (3) Career development has a significant effect on employee performance at PT Atelier 6 Jakarta.